Comparative Analyses of Antibiotic Resistance Genes in Jejunum Microbiota of Pigs in Different Areas - Li, Yongxiang; Yang, Yuting; Ma, Li; Liu, Jianping; An, Qingcong; Zhang, Chunyong; Yin, Gefen; Cao, Zhenhui; Pan, Hongbin (Frontiers in Cellular and Infection Microbiology, 2022)
Antibiotic resistance genes (ARGs) are emerging environmental contaminants that threaten human and animal health. Intestinal microbiota may be an important ARG repository, and intensive animal farming is a likely contributor to the environmental burden of ARGs. Using metagenomic sequencing, we investigated the structure, function, and drug resistance of the jejunal microbial community in Landrace (LA, Kunming), Saba (SB, Kunming), Dahe (DH, Qujing), and Diannan small-ear piglets (DS, Xishuangbanna) from different areas in Yunnan Province, China. Remarkable differences in jejunal microbial composition were revealed among the different pig breeds, while the microbial flora of LA, SB and DH in areas with close geographical location, tend to be similar. Functional analysis showed that there were abundant metabolic pathways and carbohydrate enzymes in all samples. In total, 32 487 ARGs were detected in all samples, which showed resistance to 38 categories of drugs. It is found that the abundance of ARGs has nothing to do with pig breeds, but is closely related to geographical location. There is no difference in ARGs abundance of pigs in the same area, but significant difference among pigs in different areas. Correlation analysis shows that Lactobacillus is an important ARGs producing bacterium. This comparative study not only helps to better understand the composition and function of the jejunal microflora in different pig breeds, but also provides a reference for the rational use of antibiotics and reduction of environmental pollution in animal husbandry at different areas.